Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
The EEFSEC gene encodes eukaryotic elongation factor selenocysteine-tRNA-specific, an essential component of the selenoprotein biosynthesis machinery required for normal neurodevelopment. Biallelic EEFSEC variants have recently been associated with a rare autosomal recessive neurodevelopmental disorder with variable neurological severity. Here, we describe a Turkish proband carrying the recurrent homozygous EEFSEC (NM_021937.5) variant c.1169A>C; p.Asp390Ala, together with his younger brother, who was identified with the same homozygous variant through familial testing. The proband presented with intellectual disability, delayed motor and expressive language development, mild hypotonia, subtle dysmorphic features, and self-limited early childhood febrile seizures. Compared with previously reported Turkish patients carrying the same variant, his absence of ocular motor involvement, normal neuroimaging, lack of persistent epileptiform abnormalities, and partial developmental gains suggest a relatively milder neurological presentation. The younger brother was initially identified before overt neurological manifestations and subsequently showed delayed expressive language development during early follow-up. This report provides comparative data on the recurrent EEFSEC p.Asp390Ala variant and highlights the value of familial testing, early molecular diagnosis, and longitudinal developmental monitoring in families with confirmed biallelic EEFSEC variants.